Phytochemical Screening and Antinociceptive Activity of the Hydroalcoholic Extract of Potentilla reptans L. - Somayeh Shahani; Hossein Bakhshi Jouybari; Ali Davoodi; Nematollah Ahangar (Mazandaran University of Medical Sciences, 2021)
Background: Potentilla species have traditionally been used as anti-inflammatory and analgesic agents in Iran and other countries. Objectives: This study aimed to investigate the antinociceptive effect of Potentilla reptans L., which has a wide distribution in the north of Iran. Methods: The biological activities of the hydroalcoholic extract of P. reptans aerial parts have been investigated using the acetic acid-induced writhing, hot plate, and rotarod tests in the male mice. In addition, the phytochemical profile of the extract has been evaluated. Results: The phytochemical investigation detected secondary metabolites such as flavonoids, saponins, triterpenoids, and tannins in the extract. Moreover, the Mean±SD total phenolic and tannin contents of the extract were 251±2.08 and 111.5±1.3 mg gallic acid equivalents per gram of dried extract, respectively. Also, the Mean±SD total flavonoid content was 29.42±3.31 mg quercetin equivalents per gram of dried extract. Oral administration of the extract (100, 300, and 500 mg/kg) dose-dependently reduced the number of writhing responses induced by acetic acid and increased the reaction time in the hot-plate test. The antinociceptive effect of the extract, similar to morphine, was significantly antagonized by naloxone (4 mg/kg; IP) in the writhing test. In the rotarod test, none of the extract doses used in the experiment caused a loss of locomotor activity. Conclusion: In this study, the hydroalcoholic extract of P. reptans showed a practical antinociceptive effect in hot plate and writhing tests. It seems that opioid receptors mediate the observed effect.